The significance of Pesantren Moderate Islamic Education on Islamic Studies in Indonesia - Shulhan; Samsul Ar; Hasan Asy’ari Najmuddin; Achmad Bahrur Rozi (Edukasia Islamika : Jurnal Pendidikan Islam, 2023)
This research aimed to examine moderate Islamic education's role in developing Islamic studies in Indonesia. Pesantren education has proven its worth by graduating many students working in various professions, including as lecturers in Islamic studies at Islamic higher education. This study employed a qualitative approach where the researcher served as the primary data collector. The researcher collected data using interviews, observations, and conclusions using six stages of data management. The research findings have exposed the following: First, Islamic education deepens Islamic insight by studying the yellow book and internalizing moderate Islamic values in student interactions. The depth of methodology, practicing openness, and developing a growth mindset are three strengths of moderate Islam in pesantren. Second, alums who work as lecturers consistently become mouthpieces of religious moderation through lectures, community service, thought synthesis dissemination, scientific development, and institutional development. Thus, with its advantages, moderate Islamic education in pesantren can produce national figures who influence the dynamics and progress of Islamic studies in universities.